Negotiating Work-Life Balance: A Sociological Literary Analysis of the Protagonist’s Struggles in Almira Bastari's Home Sweet Loan - Feby Rahmadhani; Sri Wulan; Asnani Asnani (JOURNAL OF LANGUAGE, 2026)
This research analyzes the protagonist's struggle in pursuing work-life balance in Almira Bastari's novel Home Sweet Loan. Using a qualitative descriptive method with sociology of literature approach, the study explores how Kaluna, the protagonist, experiences multidimensional struggles to navigate between professional responsibilities and personal life. The analysis identifies three main struggles based on Jay Shetty's framework: internal struggle (emotional and psychological conflict), external struggle (social and economic pressures), and existential struggle (search for meaning and identity). Set in urban Jakarta, the novel reflects real challenges faced by middle-class working women, including unrealistic social expectations, limited income, and familial burdens. Kaluna's strategies, such as extreme frugality and disciplined budgeting, show her resilience in maintaining control over her life amid external demands. The findings reveal that work-life balance is not a stable condition but a continuous negotiation, often filled with sacrifice and emotional tension. The protagonist's journey provides a critical lens on the social structures that burden women with invisible labor and unacknowledged emotional exhaustion. This research contributes to literary studies by highlighting how contemporary Indonesian fiction mirrors socio-economic realities, especially those experienced by young women in urban settings.